OsNCED3 and OsPYL1 promote the closure of rice florets by regulating sugar transporters through endogenous abscisic acid - Xiawan Zhai; Wenbin Kai; Youming Huang; Jinyin Chen; Xiaochun Zeng (Journal of Integrative Agriculture)
Rice is the world’s largest food crop, but it often encounters flowering asynchronization problems during hybrid rice seed production. In addition, the slow closure of female florets leads to seed mildew and affects the quality. The hormone abscisic acid (ABA) plays a crucial role in plant responses to abiotic stresses. Previous studies showed that exogenous ABA promotes floret closure, although the molecular mechanisms and effects of endogenous ABA on floret closure remain unknown. In this study, the effect of endogenous ABA on floret closure and the molecular mechanism by which ABA promotes floret closure through sugar transporters were investigated by changing the expression levels of OsNCED3 and OsPYL1 in rice. The results showed that overexpression (OE)-OsNCED3 increased the endogenous ABA level of florets. Florets closed 5.91 min earlier and OsNCED3 gene knockout line delayed the closure of florets by 5.08 min compared with the wild type. In addition, OsPYL1 regulated the endogenous ABA content and changed the sensitivity to ABA such that the floret closure times for OE and CRISPR-Cas9 (CR) were 9.84 min earlier and 12.78 min later, respectively, resulting in an increase in the split husk rate to 15.4%. The gene expression levels of some sugar transporters (STs) changed. The OsPYL1 and OsSWEET4 proteins could interact on the cell membrane. These results indicate that ABA promotes the closure of rice florets and the enhanced sensitivity to ABA promotes this effect even more. The molecular mechanism is mainly related to downstream sugar transporters that respond to the ABA signaling pathway, especially OsSWEET4.